CONTEXTUAL MEANING OF HAPPIER AND DRIVERS LICENSE SONG LYRICS BY OLIVIA RODRIGO: SEMANTICS STUDY - Fristi Arfiawati; Shinta Wijaya (Jurnal Sastra - Studi Ilmiah Sastra, 2025)
This study investigates the relationship between students’ self-assessment and their actual performance on the TOEFL test within the context of TOEFL preparation classes. Using a descriptive analysis approach, the research aims to explore how accurately students can predict their own TOEFL scores and what this reveals about their self-awareness and readiness for the test. Data were collected from a sample of university students enrolled in a TOEFL preparation course, who were asked to estimate their expected TOEFL scores prior to taking the actual test. The results were then compared to their real TOEFL scores. The findings indicate a significant variation between predicted and actual scores, with many students either overestimating or underestimating their performance. These discrepancies suggest that while self-assessment can be a useful reflective tool, it may not always align with objective outcomes. The study highlights the importance of guided self-assessment practices in language learning environments to improve students’ metacognitive skills and test preparedness.